Antigenic Relationships Among Strains of Vibrio parahaemolyticus - Twedt, R. M. (1972)
The antigenic relationships of 79 strains of Vibrio parahaemolyticus representing 46 assigned K-types were studied by tube agglutination. Homologous titers of 46 anti-K sera ranged from 80 to 2,560. All but three sera exhibited from one to six heterologous reactions, the majority of which gave titers of ≤20, but 19 sera showed cross-reactions whose titers exceeded 40. Nine reciprocal and 16 unilateral relationships were described. Some of the cross-reactions involved heat-extractable K-antigens, as determined by absorption with nonheated and heated heterologous antigens, whereas others did not involve K-antigens since absorption with the heterologous antigens had no effect on the homologous systems. On the basis of the reactions of selected antisera to the O-antigens of some of the K-strains, the cross-reactions could not be explained solely on the basis of O-specificities.